Reproductive Strategies of the Seagrass Zostera japonica Under Different Geographic Conditions in Northern China - Yue, Shidong; Zhang, Xiaomei; Xu, Shaochun; Zhang, Yu; Zhao, Peng; Wang, Xiaodong; Zhou, Yi (Frontiers in Marine Science, 2020)
Seagrasses are submerged marine angiosperms capable of both sexual reproduction and asexual reproduction through subsurface rhizome elongation. The amounts of sexual and asexual reproduction differ within some species depending on geographic location and environmental conditions. Here, we studied the reproductive strategies of different geographic Zostera japonica populations, S1 and S2 at Swan Lake lagoon (SLL) and H1 and H2 at Huiquan Bay (HQB), in northern China. The duration of flowering at SLL was longer than at HQB, whereas flowering initiation at HQB occurred earlier than at SLL. In addition, the timing of seed maturation at HQB occurred earlier than at SLL. The maximum reproductive effort at S2 was greater than at other sites. The maximum potential seed production was greatest at S2 (50222.17 seeds · m−2), followed by S1 (37093.94 seeds · m−2), H2 (20550.44 seeds · m−2) and H1 (9003.44 seeds · m−2). The seasonal changes in total shoot density and biomass were small at HQB. There was a relatively large number of overwintering shoots at HQB because of the higher average temperature during winter. The allocation to sexual reproduction was lower than at SLL, and no seedlings were observed at HQB during our study. Thus, the population of Z. japonica at HQB was maintained by asexual reproduction. Compared with HQB, the amount of overwintering shoots at SLL was less than 30 g dry weight · m−2. The Z. japonica at SLL relied on asexual and sexual reproduction to maintain the population. The results show the necessity of understanding local reproductive strategies before starting restoration and management projects. The study provides fundamental information and guidance for the conservation and restoration of seagrass beds.